PENGARUH PERSEPSI DAN MOTIVASI MAHASISWA AKUNTANSI TERHADAP MINAT MEMILIH KONSENTRASI PERPAJAKAN - Afif Luqman Hakim (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
This study aimed the effect of perceptions and motivations of students of Accounting Department, Faculty of Economic and Business Brawijaya University on the interest in choosing taxation concentration. The subjects of this study were 100 active students of the Department of Accounting, the concentration of taxation, Faculty of Economics and Business, Brawijaya University. Data for this study were collected using questionnaires through Google Form media and analysis using multiple linear regression with SPSS. The results showed that students' perceptions had a positive effect on interest in choosing tax concentration. Student motivation has a positive effect on interest in choosing tax concentration. Keywords : Perseption, motivation, interest, taxation